2011
DOI: 10.1375/twin.14.5.433
|View full text |Cite
|
Sign up to set email alerts
|

The Heritability of Premenstrual Syndrome

Abstract: We aimed to determine (1) the prevalence of premenstrual syndrome in a sample of twins and (2) the relative contribution of genes and environment in premenstrual syndrome. A group of 193 subjects inclusive of same gender twins (n = 176) and females from opposite sex twin sets (n = 17) entered the study. Heritability analysis used same gender twin data only. The probandwise concordance rate for the presence or absence of premenstrual syndrome was calculated and the heritability of premenstrual syndrome was asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 17 publications
0
32
0
1
Order By: Relevance
“…Taylor et al (5) studied the progesterone receptor gene and 37 SNP loci in upstream and downstream regions and found that the polymorphisms of the progesterone receptor gene were associated with a young menarche age and excessively short menstrual cycle. Furthermore, the risk for PMS has been found to be higher in identical twins than in fraternal twins (6), and mutation of the FSH-R gene may lead to amenorrhoea, infertility or premature ovarian failure (7). These results indicate that genetic susceptibility is significant to MD occurrence.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Taylor et al (5) studied the progesterone receptor gene and 37 SNP loci in upstream and downstream regions and found that the polymorphisms of the progesterone receptor gene were associated with a young menarche age and excessively short menstrual cycle. Furthermore, the risk for PMS has been found to be higher in identical twins than in fraternal twins (6), and mutation of the FSH-R gene may lead to amenorrhoea, infertility or premature ovarian failure (7). These results indicate that genetic susceptibility is significant to MD occurrence.…”
Section: Discussionmentioning
confidence: 99%
“…Taylor et al (5) found that polymorphisms in the progesterone receptor gene were associated with young menarche ages and excessively short menstrual cycles. The probability of premenstrual syndrome (PMS) has been found to be higher in identical twins than in fraternal twins (6), and mutation of the follicle-stimulating hormone receptor (FSH-R) gene may lead to amenorrhoea, infertility or premature ovarian failure (7). These findings indicate that genetic susceptibility is significant in the occurrence of MDs.…”
Section: Introductionmentioning
confidence: 99%
“…Elde edilen bu bulgunun aksine, literatürde özel-likle göğüslerde ve duyarlılık şeklinde kendini belli eden şişkinlik hissinin DDB'lerle doğrudan ilişkili olduğunu gösteren çalışmalar vardır. [34][35][36] PMS ve DDB ilişkisiyle ilgili olarak yapılan genel araştırmalar, PMS'li kadınlarda BB riskinin daha yüksek olduğunu öne sürmüştür. BB ve PMS'nin birlikte bulunduğu durumlarda duygudurum oynaklığı, öfke, irritabilite, bipolarite bulgularında sık relaps ve terapötik yanıtın daha olumsuz olduğu bildirilmiştir.…”
Section: Discussionunclassified
“…Publications of the study focused on age of menarche, premenstrual syndrome, menstrual characteristics, and reproductive health of opposite sex twins (Jahanfar, 2012a(Jahanfar, , 2012bJahanfar et al, 2011Jahanfar et al, , 2012.…”
Section: Research Backgroundmentioning
confidence: 99%
“…The twin registry also holds ceremonies, activities, and public forums for twins, such as the Family Campaign, where families with twins inclusive of parents and children participate to become familiar with the twin registry, and to support mothers pregnant with twins. (Jahanfar, 2012a(Jahanfar, , 2012bJahanfar et al, 2011Jahanfar et al, , 2012. The results of reproductive health studies were also presented at several scientific gatherings (Jahanfar, 2010a(Jahanfar, , 2010b(Jahanfar, , 2011a(Jahanfar, , 2011b(Jahanfar, , 2011c.…”
Section: Accomplishmentsmentioning
confidence: 99%